Real-world effectiveness of long-acting antipsychotic treatments in a nationwide cohort of 3957 patients with schizophrenia, schizoaffective disorder and other diagnoses in Quebec. Issue 11 (November 2018) - Stip, Emmanuel; Lachaine, Jean
Background: Long-acting injectable antipsychotics (LAI-AP) for patients with schizophrenia (SCZ) have saved significant healthcare costs. However, the cost effectiveness of LAI-AP for patients with other mental disorders has yet to be established. The goal of this study was to evaluate the impact of early initiation of LAI-AP medications on healthcare resource utilization (HRU). Drawing on the Quebecois universal healthcare program (RAMQ), we conducted a nationwide prospective cohort study of LAI-AP under real-world conditions. Methods: This study was performed using a representative sample of patients newly treated with LAI-AP ( n = 3957) who were covered by the Québec Health Insurance Plan. The index date was defined as the date of the first prescription for LAI-AP between 1 January 2008 and 31 March 2012. We collected (a) the demographics and patient characteristics; (b) the treatment characteristics index drug, speciality of the principal prescriber, prescriptions of LAI-AP; and (c) HRU and costs. Two comparisons were made between (a) non-SCZ users of LAI-AP and SCZ users of LAI-AP; and (b) patients with SCZ using first-generation antipsychotic LAI-AP (FGA-LAI) and second-generation antipsychotic LAI-AP (SGA-LAI). Results: In the people with SCZ group, 976 patients were on an SGA-LAI, and 1020 patients were on an FGA-LAI; 41.9% of all users were on risperidone LAI-AP during this period and 17.9% were on zuclopenthixol decanoate. The number of hospitalizations was reduced by half. Durations were also significantly reduced. The total healthcare cost savings for all users were C$29, 876 per patient/per year. Younger patients tended to receive more SGA-LAI than FGA-LAI: 29% versus 13%. The percentage of general practitioners who prescribe LAI-AP is higher in the FGA-LAI group than in the SGA-LAI group: 19% versus 13%. For psychiatrist prescribers, it is the opposite: 86% (SGA-LAI) versus 79% (FGA-LAI). The concomitant use of oral antipsychotics (OAP) in the year following index date is higher in the FGA-LAI group: 75% versus 43%. The number of hospitalization days was reduced by 31.5 days in the FGA-LAI group and 38.8 days in the SGA-LAI group. Cost savings were of C$31, 924 in the FGA-LAI group and of C$39, 100 in the SGA-LAI group. Conclusion: The initiation of LAI-AP saved significant costs to the province of Québec compared with the previous year. Initiation of a LAI-AP resulted in lower resource use. Higher medication costs were offset by lower inpatient and outpatient costs.